2022
DOI: 10.3390/app12020797
|View full text |Cite
|
Sign up to set email alerts
|

The Urban CoCreation Lab—An Integrated Platform for Remote and Simultaneous Collaborative Urban Planning and Design through Web-Based Desktop 3D Modeling, Head-Mounted Virtual Reality and Mobile Augmented Reality: Prototyping a Minimum Viable Product and Developing Specifications for a Minimum Marketable Product

Abstract: Both policy and research highlight the importance of diverse stakeholder input in urban development processes but visualizing future built environments and creating two-way design communication for non-expert stakeholders are challenging. The present study develops an intuitive and simplified 3D modeling platform that integrates web-based desktop, virtual reality and mobile augmented reality technologies for remote simultaneous urban design collaboration. Through iterative prototyping, based on two series of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Schubert et al (2015) explored how to combine volumetric models and hand-drawn sketches in the early design phases with the context of real sites, which provides a new way for the public to view architectural and urban designs. Imottesjo and Kain (2022) used the urban CoCreation Lab MVP, a desktop web-based 3D modeling platform, to build models which could be placed on real sites by users for observation, and which permitted multiple participants to work on the same model at the same time by frequently uploading the AR model to a cloud server. This study also suggested that the evaluation of the minimum level of detail in 3D modeling is necessary for environmental impact simulation.…”
Section: Augmented Reality Application In Urban Designmentioning
confidence: 99%
“…Schubert et al (2015) explored how to combine volumetric models and hand-drawn sketches in the early design phases with the context of real sites, which provides a new way for the public to view architectural and urban designs. Imottesjo and Kain (2022) used the urban CoCreation Lab MVP, a desktop web-based 3D modeling platform, to build models which could be placed on real sites by users for observation, and which permitted multiple participants to work on the same model at the same time by frequently uploading the AR model to a cloud server. This study also suggested that the evaluation of the minimum level of detail in 3D modeling is necessary for environmental impact simulation.…”
Section: Augmented Reality Application In Urban Designmentioning
confidence: 99%
“…Virtual and Augmented Reality (VR/AR) technologies offer immersive experiences that greatly improve stakeholder engagement (Theguardian, 2024) (Imottesjo & Kain, 2022). Construction managers can use these technologies to provide stakeholders with virtual walkthroughs of the project, allowing them to visualize the final outcome and make informed decisions.…”
Section: Adopting Virtual and Augmented Reality (Vr/ar) For Stakehold...mentioning
confidence: 99%
“…[2022], experimenting with the notion of AI's effect on education was the goal of this investigation. It is clear what the ethical implications are, as well as a set of suggestions for implementing AI-assisted teaching and learning in practise [23]. According to Sepasgozar [2022], case-based storytelling is the teaching method used in the development and implementation of new virtual tour models for on-the-job training.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%